Effect of Casein Phospopeptide-Amorphous Calcium Phospate (CPP-ACP) on Demineralized Deciduous Enamel. - rachmawati, dini; Kurniawati, Chandrasari; Hakim, Lukman; Roeswahjuni, Neny (E-Prodenta Journal of Dentistry, 2019)
Casein Phophopeptide-Amorphous Calcium Phospahte (CPP-ACP) is a material in the field of dentistry that contains casein in the form of Casein Phosphopeptide (CPP), a high level of calcium and phosphate that’s capable to slow down demineralization. CPP-ACP is able to localized calcium ion and phosphate on tooth surface to help maintain neutral condition on dental enamel so buffer process by saliva is secured and remineralization process happened which can been seen through several factors such as dental enamel hardness, dental enamel morphology structure, and enamel translucency. Objective: the purpose of this study is to understand the remineralization effect of CPP-ACP on demineralized enamel of deciduous teeth. Methods: This study is experimental study with pre- and post-test control group using 2 maxillary incisive groups. Control group is soaked in mineral water for 14 days, and treatment group is soaked in soft drinks for 14 days, then CPP-ACP is applicated for 14 days. Result: Shown that CPP-ACP application increase calcium and phosphate levels on demineralized maxillary deciduous incisive teeth. Conclusion CPP-ACP can be used as alternative remineralization material on deciduous teeth.Keywords: CPP-ACP, Remineralization, Demineralization